On Misspecification of Spatial Weight Matrix for Small Area Estimation in Longitudinal Analysis; O błednej specyfikacji macierzy wag przestrzennych w statystyce małych obszaroẃ w badaniach wielookresowych - Tomasz Zȧdło (Comparative Economic Research. Central and Eastern Europe, 2012)
The problem of prediction of subpopulation (domain) total is studied as in Rao (2003). Considerations are based on spatially correlated longitudinal data. The domain of interest can be defined after sample selection what implies its random sample size. The special case of the General Linear Mixed Model is proposed where two random components obey assumptions of spatial and temporal moving average process respectively. Moreover, it is assumed that the population may change in time and elements' affiliations to subpopulation may change in time as well. The proposed model is a generalization of longitudinal models studied by e.g. Verbeke, Molenberghs (2000) and Hedeker, Gibbons (2006). The best linear unbiased predictor (BLUP) is derived. It may be used even if the sample size in the subpopulation of interest in the period of interest is zero. In the Monte Carlo simulation study the accuracy of the empirical version of the BLUP will be studied in the case of correct and incorrect specification of the spatial weight matrix. Two cases of model misspecification are studied. In the first case the misspecified spatial weight is used. In the second case independence of random components is assumed but the variable which is used to compute elements of spatial weight matrix in the correct case will be used as auxiliary variable in the model. – – Rozwazȧny jest problem predykcji wartosći globalnej w podpopulacji (domenie) podobnie jak w Rao (2003). Zaproponowano przypadek szczegoĺny Ogoĺnego Mieszanego Modelu Liniowego, gdzie dwa składniki losowe spełniaja załozėnia odpowiednio przestrzennego i czasowego procesu sŕedniej ruchomej. Proponowany model jest uogoĺnieniem modeli wielookresowych rozwazȧnych przez Verbeke, Molenberghs (2000) oraz Hedeker, Gibbons (2006). Wyprowadzona zostanie postacńajlepszego liniowego nieobciazȯnego predyktora wartosći globalnej w domenie. W badaniu symulacyjnym dokładnosćémpirycznej wersji najlepszego liniowego nieobciazȯnego predyktora była analizowana zaroẃno w przypadkach prawidłowej jak i nieprawidłowej specyfikacji macierzy wag.
Keywords: 330